2012
DOI: 10.4267/2042/46069
|View full text |Cite
|
Sign up to set email alerts
|

DDC (dopa decarboxylase (aromatic L-amino acid decarboxylase))

Abstract: This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 2.0 France Licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 78 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…Taking into account that the virus-mediated effects on the DDC protein and mRNA occur with different kinetics, especially in the case of HCV infection, where DDC protein is affected much earlier than the mRNA, we hypothesize that viruses may utilize distinct regulatory mechanisms for DDC. This is not surprising, as DDC expression and function is under the control of complicated and mostly uncharacterized mechanisms [19]. Virus-mediated DDC regulation is dependent, at least in part, on the viral RNA replication stage (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that the virus-mediated effects on the DDC protein and mRNA occur with different kinetics, especially in the case of HCV infection, where DDC protein is affected much earlier than the mRNA, we hypothesize that viruses may utilize distinct regulatory mechanisms for DDC. This is not surprising, as DDC expression and function is under the control of complicated and mostly uncharacterized mechanisms [19]. Virus-mediated DDC regulation is dependent, at least in part, on the viral RNA replication stage (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its expression in the nervous system, where it has a well-established role in neurotransmission, DDC has been purified from various peripheral organs, including the liver [8,9,10,11,12,13,14,15]. Although the physiological function of DDC in the periphery remains unclear [16,17,18], alterations in its expression have been reported in several malignancies such as small-cell lung and gastric cancer [19]. In human placenta, a naturally occurring inhibitor of DDC was identified as Annexin V [20].…”
Section: Introductionmentioning
confidence: 99%
“…After reverse transcription (RT), real-time quantitative PCR (qPCR) was performed in cDNA reactions using the SYBR Green-based Luna 1 Universal qPCR Master Mix (New England Biolabs) as well as primer pairs specific for DDC, ACE2, dACE2, ISG56 and EPO (Table 1), previously validated [5,12,[31][32][33], or the cell type marker genes EPCAM, CD45, CD74 and LYN (S1 Table ). The primers for DDC bind to exons 10 and 12, and detect the majority of the known DDC mRNA isoforms [8,34]. The house-keeping gene 14-3-3-zeta polypeptide (YWHAZ) was used as a normalization control.…”
Section: Rna Quantification By Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Analysis of a large number of human microarray datasets from various tissues revealed that the L-Dopa decarboxylase (DDC) gene exhibited the most statistically significant co-expression link with ACE2 locus [7]. DDC catalyzes decarboxylation reactions, among them the conversion of L-3,4-dihydroxyphenylalanine (L-Dopa) to the immune-modulatory catecholamine dopamine [8,9] and of 5-hydroxytryptophan to the inflammation and immunity regulator serotonin [10]. Both dopamine and serotonin act also as neurotransmitters providing a linkage between immune and neuron systems [11].…”
Section: Introductionmentioning
confidence: 99%
“…DDC is localized both in the cytosol and cell membrane [ 14 ]. Enzymatically active DDC has already been detected in brain, liver, kidney, adrenal glands, pancreas, cervix [ 15 ], placenta [ 16 ], as well as in peripheral leukocytes and T-cells [ 17 ]. The presence of DDC activity in leukocytes and in the histiocytic lymphoma cell line U-937 implies a cross-talk between the nervous and the immune system, and raises new questions about the regulatory role of DDC in immune responses [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%